Definition, roles, and potential research issues of the metaverse in education: An artificial intelligence perspective - Hwang, Gwo-Jen; Chien, Shu-Yun (Computers and education. Artificial intelligence, 2022)
The metaverse has been recognized as one of the technologies with the greatest potential today. However, the use of the metaverse for educational purposes is seldom discussed. Most educators might be unaware of the features of the metaverse, not to mention the potential applications of this emerging technology. In this position paper, we aim to provide a clear definition of the metaverse. Potential applications and research issues of the metaverse in educational settings are also presented. Moreover, the roles of AI in the metaverse as well as metaverse-based education are discussed. It is expected that, via this paper, researchers from the fields of both computer science and educational technology would have a clear picture of what the metaverse is and how it can be used for educational purposes. More importantly, it is expected that more studies related to metaverse-based education can be reported in the near future.